Micro grid planning and operation - Banerjee, B.; Jayaweera, D.; Islam, Syed (2016)
© Springer International Publishing Switzerland 2016. Increasing penetrations of renewable power as well as deregulation of electricity markets have seen a rise around the world. A Micro Grid is a smaller entity that can intelligently control and coordinate distributed energy resources with the support of intelligent controllers and other necessary architecture. However, achieving such objectives that lead to a smart operation require significant advances to planning and operation of the Micro Grid as the collective operation of Micro Grids can potentially provide business cases. Roles of Micro Grids include improving reliability, resilience and security at the normal and emergency operating conditions of the power grid. Each mode of operation presents challenges such as frequency control in islanded mode and voltage control in grid connect mode. Micro Grid control strategies may be classified into grid following and grid forming and further into interactive or non-interactive. Most control hierarchies combine centralised as well as decentralised control. This chapter investigates specific challenges in a Micro Grid, planning and operation, control strategies as well as realistic studies of micro grids.